Use of crown ethers to isolate intermediates in ammonia-borane dehydrocoupling reactions. Issue 18 (8th February 2016) - Less, Robert J.; García-Rodríguez, Raúl; Simmonds, Hayley R.; Allen, Lucy K.; Bond, Andrew D.; Wright, Dominic S.
Abstract : The presence of 18-crown-6 in the Lewis acid-promoted dehydrocoupling reaction of ammonia borane permits isolation of [(THF)BH2 NH3 ] + cation. Abstract : The presence of 18-crown-6 in the Lewis acid-promoted dehydrocoupling reaction of ammonia borane permits isolation of [(THF)BH2 NH3 ] + and [BH2 (NH3 )2 ] + cations. [(THF)BH2 NH3 ] + reacts with Lewis bases to give either boron adducts or by deprotonation at nitrogen to give borazine and ammonia-borane.